Implementation of the Peace Deed (Acte van Dading) as a Settlement of Civil Disputes through a Simple Lawsuit Process at the Padang District Court - Partynia Nur Imantya; Elwi Danil; Wetria Fauzi (Journal of Law, Politic and Humanities, 2025)
A peace deed is a legal instrument that has binding force and permanent legal force, equivalent to a court decision that cannot be appealed or appealed. In the practice of resolving civil disputes, peace deeds play an important role in providing fast, simple, and low-cost solutions, especially in the context of simple lawsuits. This study aims to examine two main aspects, namely (1) how the implementation of the peace deed as a method of resolving civil disputes through a simple lawsuit at the Padang District Court, and (2) the legal consequences that arise if one of the parties commits a default on the content of the peace deed. Using an empirical juridical research method, this study processed primary and secondary data through literature studies and interviews with related parties. The results of the study show that the simple lawsuit mechanism provides efficiency in resolving civil disputes, both in terms of time and cost. In addition, if one party commits a breach of the peace deed, the other party can immediately submit an application for execution to the court without the need to file a new lawsuit. These findings confirm that peace deeds have a strategic function in accelerating the resolution of civil disputes and strengthening legal certainty for the parties to the dispute